Prosiding Seminar Nasional 2018 “ Peran Dan Tanggung Jawab Tenaga Kesehatan Dalam Mendukung Program Kesehatan Nasional” 2019
DOI: 10.32528/psn.v0i0.1726
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Keluarga Menjadi Keluarga Tanggap Hipertensi (Lugas) Di Dusun Durmo, Desa Bantur, Kecamatan Bantur

Abstract: Hypertension is one of number one causes of death in the world. The prevalence of hypertension has increased every year along with increasing age, level of education, non-working status and high level of per capita expenditure. Malang Regency is one of the regions in Indonesia with the number one of hypertensive patients. Completion of hypertension problems in Malang Regency until now has not met the 100% target. The lowest coverage achievement in Bantur District is in Bantur Village. This community service pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Multiple components, found in the scientific literature, were also mentioned in the grey literature; namely, appointing CHWs, family support, comprehensiveness, physical exercise, telehealth and education [ 38 , 51 , 57 – 59 , 62 , 65 , 68 ]. Hung [ 62 ] also reported that telehealth , by providing online communication tools on a website, promotes communication between patients and the health system in rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple components, found in the scientific literature, were also mentioned in the grey literature; namely, appointing CHWs, family support, comprehensiveness, physical exercise, telehealth and education [ 38 , 51 , 57 – 59 , 62 , 65 , 68 ]. Hung [ 62 ] also reported that telehealth , by providing online communication tools on a website, promotes communication between patients and the health system in rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Adapuan hasilnya sebagai berikut: Promosi kesehatan tentang pernikahan muda saat ini menjadi upaya pencegahan terjadinya faktor stunting di masyarakat (Wicaksono & Alfianto, 2020). Beberapa upaya yang dapat dilakukan dengan cara pencegahan baik pada kelompok-kelompok remaja hingga orang tua untuk menekan terjadinya pernikahan muda (Sezgin & Punamäki, 2020).…”
Section: Hasil Dan Pembahasanunclassified